Prospects for the development and use of Unmanned Aerial Systems - Leszek Cwojdziński (Przegląd Komunikacyjny)
Abstract: This article presents the basic assumptions concerning the prospects for the use and development of unmanned flying systems. Data on the use of combat flying platforms are presented. At the same time, the directions of development and use of civil and combat air systems in tasks for the benefit of the national economy and future armed conflicts were presented. It was indicated that unmanned aerial systems, the use of which brings significant financial benefits, are a type of weapon that changes the approach of UAV users in the most spectacular way, transforming the face of their civil and military application. The use of unmanned aerial vehicles as part of combat tasks and missions forces continuous development personnel in terms of the ability to perform complex tasks related to both civil and military use. At the same time influencing the change of tactics of using unmanned combat systems. On the basis of analyzes and comparisons, the author also proposes that the development work and construction of elements and systems for unmanned aerial platforms become an opportunity for the development of national research institutes and the defense industry, which should consequently be the main supplier of basic types of modern weapons.. Keywords: Unmanned aerial vehicle; UAV; Quadrocopter; Drone; Multisensor technologies; AI; UAV; Stealth